2021
DOI: 10.1186/s12978-021-01241-5
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing respectful maternity care at the healthcare provider level: a systematic scoping review

Abstract: Background Ensuring the right to respectful care for maternal and newborn health, a critical dimension of quality and acceptability, requires meeting standards for Respectful Maternity Care (RMC). Absence of mistreatment does not constitute RMC. Evidence generation to inform definitional standards for RMC is in an early stage. The aim of this systematic review is clear provider-level operationalization of key RMC principles, to facilitate their consistent implementation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…Due to the normalization of the culture of technocratic and overmedicalized care, it is likely that health workers are not even aware that they are perpetrating OV. This was confirmed in global literature citing that the chief barriers to improving RMC included provider attitudes, misconceptions of its definition and violations, and false beliefs that expectations are met ( 65 , 67 , 73 , 74 , 82 ). Zooming out more broadly, non-dignified care, and its intersections with other abuses is embedded in socio-cultural norms.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Due to the normalization of the culture of technocratic and overmedicalized care, it is likely that health workers are not even aware that they are perpetrating OV. This was confirmed in global literature citing that the chief barriers to improving RMC included provider attitudes, misconceptions of its definition and violations, and false beliefs that expectations are met ( 65 , 67 , 73 , 74 , 82 ). Zooming out more broadly, non-dignified care, and its intersections with other abuses is embedded in socio-cultural norms.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, women from Ethiopia and India ranked this type of D&A highest, possibly due to geographical and cultural proximity to the EMR ( 79 , 80 ). Global systematic reviews found a high prevalence of verbal abuse across the high, middle, and low-income countries, with threats and judgmental attitudes being more common in LMICs, while objectification of women's bodies was reported more in M/HICs ( 19 , 21 , 81 , 82 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been no agreed global definition of RMC because it is not simply the absence of mistreatment, 10 and women’s voices should contribute to defining it. 11 The World Health Organization defines RMC as “care organised for and provided to all women in a manner that maintains their dignity, privacy and confidentiality, ensures freedom from harm and mistreatment, and enables informed choice and continuous support during labour and childbirth”.…”
Section: Introductionmentioning
confidence: 99%